A semiparametric approach for meta‐analysis of diagnostic accuracy studies with multiple cut‐offs. (24th June 2022) - Frömke, Cornelia; Kirstein, Mathia; Zapf, Antonia
Abstract: The accuracy of a diagnostic test is often expressed using a pair of measures: sensitivity (proportion of test positives among all individuals with target condition) and specificity (proportion of test negatives among all individuals without target condition). If the outcome of a diagnostic test is binary, results from different studies can easily be summarized in a meta‐analysis. However, if the diagnostic test is based on a discrete or continuous measure (e.g., a biomarker), several cut‐offs within one study as well as among different studies are published. Instead of taking all information of the cut‐offs into account in the meta‐analysis, a single cut‐off per study is often selected arbitrarily for the analysis, even though there are statistical methods for the incorporation of several cut‐offs. For these methods, distributional assumptions have to be met and/or the models may not converge when specific data structures occur. We propose a semiparametric approach to overcome both problems. Our simulation study shows that the diagnostic accuracy is under‐estimated, although this underestimation in sensitivity and specificity is relatively small. The comparative approach of Steinhauser et al. is better in terms of coverage probability, but may lead to convergence problems. In addition to the simulation results, we illustrate the application of the semiparametric approach using a published meta‐analysis for a diagnostic test differentiating between bacterial and viral meningitis in children.